Development of strategic supplier relationships through business networks. The case of Loccioni Group - Pandolfi, Cecilia Paulina (2021)
Fil: Pandolfi, Cecilia Paulina. Universidad Nacional del Litoral. Facultad de Ciencias Económicas; Argentina.